Properties of FA-CVD silica coated steel sheet after deformation: coating integrity and corrosion related forming limit curve. (November 2013) - Hausbrand, R.; van der Donck, T.; Celis, J.-P.; Clarysse, F.
Abstract : Thin silica coatings may be used as pretreatments for steel sheet, offering temporary corrosion protection and promoting adhesion of organic coatings. For use as ready to paint product, silica coated steel has to possess also good corrosion properties after deformation and successive paint application. In this paper, we investigate the forming limit curve for flame assisted chemical vapour deposited silica coated steel sheet with respect to corrosion properties after paint application. We find good corrosion properties up to a strain of 10%, indicating a high tolerance towards deformation. Evaluation of the silica coated steel sheet by scanning electron microscopy shows that severe failure takes place at high levels of deformation, but only at a fraction of the surface. Adhesion, cracking as well as deadhesion and flaking of the very thin films (15–50 nm) was furthermore investigated by scratch testing.